Pemanfaatan Bahan Galian Mineral Kalsit Berdasarkan Karakteristik Sifat Fisik di Cikembar Sukabumi - Waode Jelita Ma’ruff Bay; Linda Pulungan (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Calcite mineral is a mineral with a chemical composition of CaCO3 which can be found in a pure state or not. The purpose of this study is to analyze the characteristics of the calcite mineral and recommend its use based on the physical properties of the calcite mineral in the research area, in order to improve the economy of the surrounding area and create employment opportunities. Tests were carried out to determine the characteristics of physical and chemical properties, namely physical properties testing to determine porosity, mass (original, saturated, dependent), weight (original, dry, saturated), apparent specific gravity, true specific gravity, original water content, saturated water content, degree of saturation and void ratio, as well as petrographic thin sections to determine pore type, variety and diagenetic products. Then testing the chemical properties to determine the composition and content of the calcite mineral being tested. In the research area, through testing the physical properties and testing the chemical properties of XRF, it can be seen the characteristics of the mineral calcite which is perfectly crystallized, has orthosparite cement in BGP-1 (10%) and BGP-2 (15%) with poor grain uniformity, fine grained. – medium, the porosity of GMP-01 (3.93%) and GMP-02 (3.25%) and the results of the void ratio of 0.04 cm3 and 0.03 cm3, this value indicates that the rock has a small cavity so that the volume is large. found small. For XRF, it is known that there is 55.84% CaO in the calcite mineral. Abstrak. Mineral kalsit adalah mineral dengan kompisi kimia CaCO3 yang dapat dijumpai dalam keadaan murni ataupun tidak. Adapun tujuan dari penelitian ini untuk menganalisis karakteristik mineral kalsit dan merekomendasikan untuk pemanfaatannya berdasarkan sifat fisik mineral kalsit di daerah penelitian, guna meningkatkan perekonomian daerah sekitar serta membuka lapangan kerja. Dilakukan pengujian untuk mengetahui karakteristik sifat fisik dan sifat kimiawi, yaitu pengujian sifat fisik untuk mengetahui porositas, massa (asli, jenuh, tergantung), bobot (asli, kering, jenuh), apparent specific gravity, true specific gravity, kadar air asli, saturated water content, derajat kejenuhan dan void ratio, serta sayatan tipis petrografi untuk mengetahui tipe pori, faries dan produk diagenesa. Kemudian pengujian sifat kimiawi untuk mengetahui komposisi dan kadar pada mineral kalsit yang di uji. Pada daerah penelitian melalui pengujian sifat fisik dan pengujian sifat kimia XRF, maka dapat diketahui karakteristik mineral kalsit yang terkristalisasi sempurna, memiliki semen orthosparit pada BGP-1 (10%) dan BGP- 2 (15%) dengan keseragaman butir yang buruk, berbutir halus – sedang, porositas GMP-01 (3,93%) dan GMP-02 (3,25%) dan hasil void ratio sebesar 0,04 cm3 dan 0,03 cm3, nilai ini menunjukan bahwa batuan tersebut memiliki rongga kecil sehingga volume yang didapatkan kecil. Untuk XRF diketahui terdapat 55,84% CaO dalam mineral kalsit tersebut.